The ABO blood group genotype and factor VIII levels as independent risk factors for venous thromboembolism - Tirado, Isabel; Mateo, José; Soria, José Manuel; Oliver, Arturo; Martínez-Sánchez, Elisabeth; Vallvé, Cristina; Borrell, Monserrat; Urrutia, Teresa; Fontcuberta, Jordi (Thrombosis and Haemostasis, 2005)
Factor VIII (FVIII), von Willebrand factor (vWF) and the ABO blood groups have been associated with thrombosis. The ABO locus has functional effects on vWF and FVIII levels and is genetically correlated with FVIII, vWF and thrombosis. We carried out a case-control study to assess the role of FVIII, vWF and ABO types on thrombotic risk. We analyzed 250 patients with venous thrombosis and 250 unrelated controls. FVIII, vWF and other factors related to thrombophilia were measured, ABO groups were analyzed by genotyping. FVIII and vWF were higher in non-O individuals. Group O was more frequent in the controls (44.3% v 23.3%; difference 21.1%; 95% CI: 13.0–29.3%) and Group A in patients (59.2% v. 41.5%; difference 17.7%, 95% CI: 9.1–26.4%). Individuals carrying the A1 allele had a higher risk of thrombosis (OR 2.6; 95% CI, 1.8–3.8). The risk attributed to vWF disappeared after adjusting for the ABO group. Patients with FVIII above the 90th percentile had a high thrombotic risk (adjusted OR 3.7; 95%CI, 2.1–6.5), and a high risk of recurrence (OR 2.3; 95%CI: 1.3–4.1). In conclusion, high FVIII levels and non-O blood groups, likely those with the A1 allele, are independent risk factors for venous thromboembolism and should be considered in evaluating of thrombophilia.
Keywords: Factor VIII; ABO genotypes; von Willebrand factor; venous thrombosis; thrombophilia